Factor determinant of customer trust on Islamic car loan by moderating effect of Shari’ah compliance - Yusoff, Nur Athirah; Abdullah, Azwan; Ismail, Mohamad (Universiti Teknologi MARA, Kelantan, 2018)
Over a few decades, the existence of strong Islamic movement has created a new interest in Islamic economics. Gradually, interest-free banking by Islamic banks started to fame and the system has gained global recognition. Many bank offer similar products and services. Therefore, competition between of Islamic and conventional banks intensifies, thus, the perception of the customer will determine the level of the competitiveness and success of the banks. In Malaysia, Al-Ijarah Thumma Al-Bay (AITAB) is one of the latest innovative products of Islamic hire-purchase facility in Islamic banks in Malaysia today, which is designed to meet the hire-purchased concept on current demand of customers that focusing in motor vehicles. Therefore, this research will conducted to study and identify how customers create their trust in using the products, services of Islamic bank. Based on the existing gaps, the researcher proposes a dependent variable (i.e. Customer Trust), independent variables (i.e. Image and reputation, Customer knowledge, Marketing), and moderator (i.e. Shari’ah compliance). In this study, seven hypotheses are developed to identify the relationship between customer trust and the determinant factors. The expected result of all the factors independent variables is significant relationship on customer trust. The study will adopt convenience sampling and will apply quantitative method by distributing survey questionnaire to the customers in conventional bank. The Statistical Package for Social Scientist (SPSS) is used to analysis the data. In this study, the study is expected to develop a new framework.